Research of the formation and development of FabLab as a form of interaction of science and manufacture in Ukraine - Kozyk, Vasyl; Danylovych, Taras; Mrykhina, Oleksandra; Havryliak, Anatolii (Technology audit and production reserves, 2018)
The object of research is the process of interaction between science and production on the basis of the development of FabLab in Ukraine, the subject is the theoretical and applied bases of the formation and development of FabLab. During the processing of the research problems, the authors applied the methods and approaches: a systematic approach, methods of grouping and generalization, the method of retrospecting, methods of analysis and synthesis. The prerequisites for the emergence and spread of FabLab in the world are considered, a retrospective analysis of their development is carried out and the current state is assessed. The principles of creating FabLab are studied (requirements for the organizational structure of laboratories, management approaches, specific features of production and training activities, commercial and non-commercial functioning models, legal aspects, definition of a set of tools and tools for invention, features of FabLab created on the basis of universities, etc.). The problems of formation and reasonable prospects for the development of FabLab in Ukraine are analyzed. In particular, FabLab is considered as important elements of the innovation infrastructure of the region, designed to provide answers in the early stages of innovation. From such positions in the work, the possibilities that FabLab in Ukraine can provide are investigated. First, to promote a balanced solution of the problem of creating new jobs in the region, creating new innovative structures. Secondly, to organize the space where innovative products are generated, embodied in prototypes and tested that becomes the basis for business development on innovative principles. Thirdly, to increase the level of training of future specialists through the use of unique resources FabLab. Fourth, to promote the growth of the level of successful employment of students, interest and involvement of schoolchildren in the choice of engineering specialties, stimulation of youth entrepreneurship, and the like. Based on the results of the analysis of macroeconomic indicators, the work substantiates the role of FabLab in Ukraine in the context of the challenges of the modern technological world in revising traditional approaches in production, management and other areas of activity.